The Correlation of Price and Service Quality on Go-Jek Consumers Satisfaction In Pamulang Tangerang Selatan - Erlita Kurniawaty; Subarto Subarto; Nur Subekhan (Universitas Pamulang, 2020)
This research aims to determine value of serivce quality and price that affect customersatisfaction of go-jek services in Pamulang area of South Tangerang city from individual and generalperspective. The method used is descriptive quantitative with a sample of 100 people. Based on thetest results of hypothesis, for the variable of service quality (X1) with t arithmetic (3,555)> t table(1,988), it is obtained that the results are significant itself, that is service quality has an influence onconsumer satisfaction of go-jek services in Pamulang, South Tangerang. Similarly, for the variableprice (X2) with t arithmetic (3.182) > t table (1.988) obtained significant results on their own, namelythe price has an influence on consumer satisfaction of go-jek services in Pamulang, South Tangerang.The calculated F value (20,802) > F table (3.09) with a significance level of 0,000 < 0.05, this showsboth variables quality of service and price have an influence on customer satisfaction in Pamulangarea, South Tangerang.